Sejarah Pakaian Muslim Arab Pada Masa Islam Awal - Khoiri, Miftahul; Sodikin, Ahmad (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2023)
Abstract: This article aims to examine the history of Arab Muslim clothing in the early days of Islam which was associated with social strata in society. This article is a literature review, using historical methods, namely, heuristics, criticism, interpretation and historiography. The results of this study show that the history and development of Arab Muslim clothing during the Early Islamic period is closely related to the pre-Islamic period, although in certain respects Islam has improved, for example regarding the requirements for covering the private parts. In its development, clothing in each region has differences in how it is used. Arab people who move to a place can mix with the local people's way of dressing. The types of clothing at that time were, Al-Marth, Ad-Dir, Qamish, Al-Khimar, as well as Al-Izar and ar-Rida'. The Arab nation consists of various people such as kings, soldiers and commoners, thus creating social classes in society in clothing and clothing showing their social class. The contribution of this research provides sociological insights in understanding returned Islamic clothing in an Arabic context.Abstrak: Artikel ini bertujuan mengkaji sejarah pakaian muslim Arab pada masa Islam awal yang dikaitkan dengan strata sosial bagi masyarakat. Artikel ini merupakan kajian pustaka, dengan menggunakan metode sejarah yakni, heuristic, kritik, interpretasi, dan historiografi. Hasil kajian ini menunjukkan bahwa sejarah dan perkembangan pakaian muslim Arab masa Islam Awal terkait erat dengan masa pra Islam meskipun dalam hal tertentu Islam memperbaikinya, misalnya terkait syarat menutup aurat. Dalam perkembangannya, pakaian yang berada di setiap wilayah mempunyai perbedaan dari cara menggunakannya. Masyarakat Arab yang pindah ke suatu tempat dapat bercampur dengan cara berpakaian masyarakat setempat. Jenis pakaian saat itu yakni, Al-Marth, Ad-Dir, Qamish, Al-Khimar, serta Al-Izar dan ar-Rida’. Bangsa arab terdiri dari berbagai masyarakat seperti raja, prajurit, dan masyarakat jelata, sehingga membuat kelas-kelas sosial di masyarakat dalam berpakaian dan pakaian menunjukkan kelas sosialnya. Kontribusi penelitian ini memberikan wawasan sosiologis dalam memahami pakaian Islam yang dikembalikan dalam konteks kearaban.